Early hemi-diaphragmatic plication following intraoperative phrenic nerve transection during complete AV canal repair - Hamad Alowayshiq; Alhasan Shaban; Dunay Khaymaf; Motazz Alarfaj; Hamad Alfuraian; Khalid Assiri (Elsevier, 2018)
Unilateral diaphragmatic palsy reduces pulmonary function by about 25% in older children and usually it is well tolerated; however, it causes severe respiratory distress in infants and young children. Diaphragmatic plication performed later than 10 days after cardiac surgery for patients under 1 year of age was associated with higher incidence of pneumonia and mortality. The management of the diaphragmatic paralysis due to phrenic nerve injury aiming mainly to preserve the respiratory function. Until now, the optimal management of diaphragmatic palsy in children who have undergone cardiac surgery remains controversial and consists of prolonged ventilation or diaphragmatic plication. In our case, many factors supported early diaphragmatic plication, the age of the patient, post-operative AV canal repair with severe pulmonary hypertension, and clear transection of the left phrenic nerve diagnosed intraoperatively.